Examining the Factors Affecting CO2 Emissions from Road Transportation in Malaysia - Yuaningsih, Lilis; Febrianti, R. Adjeng Mariana; Ahmad, Munawar Javed (International Journal of Energy Economics and Policy, 2021)
Increased economic growth and transportation have led to a great increase in carbon emission in Malaysia. This paper investigates the factors such as distance travel (DT), fuel efficiency (FE), fuel price (FP) and fuel consumption as determinants of carbon emission from road transportation in Malaysia for the period 1990 to 2019. The results indicate that DT, FP, and FE are the main determinants of carbon emission. The study concludes that to reduce carbon emission in Malaysia, policies causing structural adjustments in the road transport sector of Malaysia must be implemented. Keywords: Carbon dioxide gas emissions, energy consumption, road transportation, Economic growth JEL Classification: Q19 DOI: https://doi.org/10.32479/ijeep.10957